Rancang Bangun Sistem Informasi Manajemen Proyek Departemen IT PT. Pertamina UPMS V Surabaya - Yunita Ardilla; Shinta Pramesti; Dwi Sunaryono (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Department of IT M&T PT. Pertamina UPMS V Surabaya has currently implemented a management guideline based on COBIT 5.0 to support the process of monitoring and scheduling projects that will be implemented or currently being worked on PT. Pertamina UPMS V Surabaya. But in the process of implementing management guidelines, the department of IT M&T has not maximized the implementation of the monitoring and scheduling because it does not yet have a project management information system application. So far employees from the department of IT M&T use the process of monitoring and scheduling projects manually, namely by making a report in the form of an excel file for each progress of the projects. Of course, this is considered inefficient and often encounters human errors. Therefore, a web-based project management information system application was made, the application was built using the C3 programming language and Microsoft SQL Server database. Based on observation, it was concluding that the features available in the project management information system application had been running well and were able to meet the needs of users.